Prabowo’ Conversational Implicatures in Mata Najwa’s Program - Dwi Santoso; Rahmawati (Bulletin of Science Education, 2024)
The Republic of Indonesia's potential presidential candidates first got together on September 19, 2023, at Mata Najwa's "3 Presidential Candidates Talking Ideas" event at Gadjah Mada University. This forum is very important since all potential candidates for the Republic of Indonesia's presidency must be able to fully communicate the content of their speeches. From this phenomenon, the research attempts to characterize the ways in which the cooperative principle has been violated and the conversational strategies employed by Prabowo Subianto at the "3 Bacapres Talk Ideas" event in Prabowo Subianto. The speech data from the interview between Najwa Shihab and Prabowo Subianto from Najwa Shihab's YouTube channel was used for this study. Using a pragmatic theoretical approach and qualitative descriptive approaches, particularly the notion of cooperative principles and implicatures, the data were evaluated. The research data was transcribed and gathered. The conclusion is that Prabowo Subianto tends to violate the maxim of quantity and maxim of relevance. The purpose of violating the maxim is to argue and inform.